(untitled) (Andamios, Revista de Investigación Social, 2013)
This paper analyzes the effect that political and institutional factors at the level of debt that municipalities hire annually. the analysis includes the hundred municipalities that are part of the states of Baja California, Baja California sur, Sonora and Sinaloa during the period 1989 to 2007. The empirical results obtained by testing panel data techniques on fixed and random effects. The evidence reveals that the democratization process in the states and municipalities, identified primarily through the phenomenon of divided government has a significant impact in reducing the level of municipal debt. also, the design of federalism produces effects contrary to financial balance. finally, formal institutions of control have not been efficient enough to give a proper direction to the financial requirements of municipalities.